2008
DOI: 10.2500/aap.2008.29.3179
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of nasal symptoms attributed to allergies in the United States: Findings from the burden of rhinitis in an America survey

Abstract: Although the annual prevalence of physician-diagnosed hay fever has been previously reported, the prevalence of allergic rhinitis symptoms in the United States is uncertain. The purpose of this study was to estimate the prevalence of allergic rhinitis symptoms in the United States. A self-administered 10-item screening questionnaire regarding nasal symptoms was sent to representative households in the United States in January 2004. A total of 8,708 members (44.3%) reported nasal symptoms on > or =7 days in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
115
1
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 0 publications
11
115
1
10
Order By: Relevance
“…The co-existence of allergic conjunctivitis in patients with AR is widely recognized [13,14]. In a recent study, allergic conjunctivitis was identified in 53.5% of patients with AR, a finding comparable to those from other studies [15].…”
Section: Abstract: 5-grass-pollen Tablet • Allergic Rhinitis • Allergsupporting
confidence: 73%
See 1 more Smart Citation
“…The co-existence of allergic conjunctivitis in patients with AR is widely recognized [13,14]. In a recent study, allergic conjunctivitis was identified in 53.5% of patients with AR, a finding comparable to those from other studies [15].…”
Section: Abstract: 5-grass-pollen Tablet • Allergic Rhinitis • Allergsupporting
confidence: 73%
“…Moreover, in children, AR is often comorbid with chronic middle-ear effusions, sinusitis, adenoidal and tonsillar hypertrophy and acute and serious otitis media [9]. The co-existence of allergic conjunctivitis in patients with AR is widely recognized [13,14]. In a recent study, allergic conjunctivitis was identified in 53.5% of patients with AR, a finding comparable to those from other studies [15].…”
supporting
confidence: 74%
“…Epidemiological studies have revealed that the prevalence of AR has increased progressively in the moredeveloped countries, and currently affects up to 40% of the population worldwide (12)(13)(14)(15). Likewise, rising trend of AR has also been observed globally in the past decades; with a widely varying prevalence particularly in the developing nations, including in China (16).…”
Section: Introductionmentioning
confidence: 99%
“…По данным исследования, проведенного R. Nathan и соавт. [8] в Колорадо (США), 44,3% из 8708 опрошенных пациентов отмечают симптомы ринита 7 дней и более в течение года. После прове-дения аллергологического обследования АР был диагностирован у 22% пациентов (длительность обострения составила от 7 дней и более) .…”
unclassified